Strategi Pemasaran CV. Indo Jaya Bersatu Dalam Meningkatkan Profit Perusahaan dan Menarik Minat Konsumen - Adella Desy Kurniawati; Bambang Suwarsono; Brahma Wahyu Kurniawan (FEB Universitas Maritim Semarang, 2023)
A marketing strategy consisting of product, price, promotion and distribution is a strategy that can increase company revenue and attract consumer buying interest. The aim of this research is to explain the marketing strategy of CV Indo Jaya Bersatu and its implications in increasing company profits and attracting consumer buying interest. This research is research conducted using qualitative research methods with a qualitative descriptive approach. The main data sources in this research are CV Indo Jaya Bersatu employees and CV Indo Jaya Bersatu consumers. The results of this research indicate that the 4P marketing strategy implemented by CV Indo Jayaable to increase the company's profit by increasingThe company's revenue, which was originally at IDR 5,101,243,500.00 with net income of IDR 3,197,670,700.00 in 2017, increased to IDR 7,740,548,500.00 with net income reaching IDR 6,712,445,600.00 in 2022. Growing interest among CV Indo Jaya Bersatu consumers, there is a transactional interest, namely CV Indo Jaya Bersatu consumers tend to like making transactions with CV Indo Jaya Bersatu because of the good quality and service.